Rainbow six eaudiobook - Clancy, Tom (John Clark, 2010)
Over the course of nine novels, Tom Clancy's genius for big, compelling plots and his natural narrative gift have mesmerized hundreds of millions of readers and established him as one of the preeminent storytellers of our time.  Rainbow Six , however, goes beyond anything he has done before. At its heart is John Clark, the ex-Navy SEAL of Without Remorse , a master of secret operational missions, and newly named the head of an international task force dedicated to combating terrorism. Clark is looking forward to sinking his teeth into a new mission, but the opportunities start coming faster than anyone could have expected; an incident at a Swiss bank, the kidnapping of an international trader in Germany, a  terrible raid on an amusement park in Spain. Each episode seems separate, yet the timing disturbs Clark.  Is there a connection?  He tries to figure out where all this activity is heading, but there is no way to predict the real threat: a group of terrorists like none the world has ever encountered, a group so extreme that their success could literally mean the end of life on this earth as we know it.